Faktor-Faktor Risiko Terjadinya Pneumonia pada Pasien Covid-19 Di RSUP Dr Sardjito Yogyakarta - Perwira, Rendra; Uyun, Yusmein; Widodo, Untung (Jurnal Komplikasi Anestesi, 2021)
Background: Globally, more than three million confirmed cases of COVID-19 have been reported. According to the WHO report on May 6, 2020, the number of world cases that were confirmed positive was 3 588 773, and the death toll was 247 503 people. Pneumonia appears to be one of the serious manifestations of COVID-19 infection. It is necessary to know the risk factors for COVID-19 pneumonia Methods: The study used a retrospective cohort method, the research subjects were taken from March 2020 to March 2021 with the status of inpatients and confirmed Covid-19 at Dr Sardjito Hospital. Results: In this study, the total sample was 630 patients.The results of the multivariate analysis showed that the factors of age, type II DM, hypertension and male sex were significant for COVID-19 pneumonia. Age 60 years is at risk of pneumonia 1.6 times the risk of developing pneumonia (p=0.041 OR 1.6 95% CI=1.02-2.77), DM Ttype II has a risk of COVID-19 pneumonia 2.48 times (p=0.001 OR 2.48, 95%CI=1.44-4.29), hypertension risk of pneumonia 1.68 times (p=0.042 OR 1.68, 95%CI=1.01-2.77), male gender men were at risk of pneumonia 1.74 times (p=0.004, OR 1.74, 95%CI=1.2-2.57). Conclusion: Age 60 years, hypertension, type II DM and male are significant risk factors for pneumonia in patients with COVID-19 infection.